Dexmedetomidine alleviates pain in MPTP-treated mice by activating the AMPK/mTOR/NF-κB pathways in astrocytes. (20th November 2022) - Chen, Yaohua; Li, Yuping; Li, Chunxiang; Zhu, Dan; Cheng, Oumei; Cui, Jian
Highlights: Dex attenuated MPTP-induced motor dysfunction and SN dopaminergic neuron damage of mice. Dex alleviates hyperalgesia through reducing the activation of astrocytes in the DHSC. The effect of Dex partly through the AMPK/mTOR/NF-κB pathway. Abstract: Pain is a major non-motor symptom that contributes to impaired quality of life in Parkinson's disease (PD). However, the mechanisms and treatment of pain in PD have not been well studied. Dexmedetomidine (Dex) is used for analgesia and sedation during deep brain stimulation (DBS) and may reverse the progression of PD. Here, we explored the effect of Dex on Parkinson's pain and the underlying mechanism. C57BL/6 mice were intraperitoneally injected with 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP, 30 mg/kg) to establish a PD model. Then, the mice were treated with Dex (50 µg/kg) or Compound C (CC, 10 mg/kg, AMPK inhibitor). A motor behavioral test was used to validate the PD model, and a plantar test was conducted to assess mechanical and thermal stimulation thresholds. Immunofluorescence and western blotting were used to analyze the level of tyrosine hydroxylase (TH) in the substantia nigra (SN) and the expression of c-Fos, GFAP, p-AMPK, mTOR, NF-κB, TNFα, and IL-6 in the dorsal horn of the spinal cord (DHSC). We found that mice exhibited motor dysfunction and mechanical allodynia and thermal hyperalgesia after MPTP injection, and these changes were partially reversed by Dex. Dex also reduced MPTP-induced astrocyte activation and TNFα and IL-6 expression, increased p-AMPK and reduced mTOR and NF-κB expression in DHSC. Moreover, the effects of Dex were partially reversed by the AMPK inhibitor Compound C. Conclusions: These findings reveal that Dex protects dopaminergic neurons in PD and alleviates pain by reducing the activation of DHSC astrocytes through the AMPK/mTOR/NF-κB pathway. Therefore, Dex may be a potential drug for treating Parkinson's pain.